Pengaruh Rasio Likuiditas, Profitabilitas, dan Solvabilitas terhadap Keputusan Investasi dengan Ukuran Perusahaan sebagai Moderasi: Studi Kasus Perusahaan Menufaktur di Bursa Efek Indonesia - Salsabila Indah Arti Pratama; Chara Pratami T (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to examine the effect of liquidity, profitability, and solvability ratios on investment decisions while also investigating the moderating role of firm size in this relationship. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange for 2019-2023, which are marked by significant economic disruptions, including the COVID-19 pandemic. A quantitative approach was employed, using panel data regression to test the proposed hypotheses. Financial ratios were measured using the current ratio, return on assets, and debt-to-equity ratio, while investment decisions were assessed using the price-earnings ratio. The natural logarithm of total assets measured firm size. The results reveal that liquidity and solvability significantly influence investment decisions, while profitability does not. Firm size was found to moderate the relationship between liquidity and solvability with investment decisions, but not the relationship involving profitability. These findings have practical implications for investors and corporate managers in formulating investment strategies and managing financial performance, highlighting the importance of considering firm size when evaluating the effectiveness of economic indicators. This research also contributes to the empirical literature on investment decision-making in the manufacturing sector.